ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN AUDITOR PADA PERUSAHAAN SEKTOR KEUANGAN DI BURSA EFEK INDONESIA - Nababan, Innes H.; Sunarto Wage (SCIENTIA JOURNAL, 2021)
This research aims to understand and analyze the impact of audit delays, financial distress, and management turnover on auditor switching of financial companies listed on the Indonesian Stock Exchange from 2016 to 2020. The data analysis method used is deskriptif statistics and logistic regression analysis using the SPSS 25 program. The study population is 45 companies. The sample selection method uses purposive sampling, and as many as 11 companies have been obtained from 2016 to 2020. The type of data used in the study is second-hand data in the form of company financial statements. The results of this research partly show that the significant impact of audit delay on auditors switching is 0.016<0.05, financial distress has no effect on auditors switching is 0,444>0,05. while the impact of management turnover on the auditor switching is not significant, that is, 0.110>0.05. The results of this research also show that audit delays, Financial distress and management turnover have a significant impact on auditor switching, with a significant value of 0.039 <0.05.